Effect of linker substituent nature on performance of active sites in UiO-66: combined FT-IR and DFT study - Torbina, Viktoriia V.; Salaev, Mikhail A.; Paukshtis, Еvgeny A.; Liotta, Leonarda Francesca; Vodyankina, Olga V. (International journal of molecular sciences)
The nature of organic linker substituents plays an important role in gas sorption and separation as well as in catalytic applications of metal–organic frameworks. Zirconium-based UiO-66 is one of the most tunable members of this class of materials. However, the prediction of its properties is still not a fully solved problem. Here, the infrared spectroscopic measurements using highly sensitive CO probe molecules, combined with DFT calculations, are used in order to characterize the performance of different acidic sites caused by the presence of different organic linker substituents. The proposed model allowed differentiation between various active sites over the UiO-66 and clarification of their behavior. The experimental IR bands related to CO adsorption can be unambiguously assigned to one type of site or another. The previously undescribed highly red-shifted band is attributed to CO adsorbed on coordinatively unsaturated zirconium sites through an O atom. The results confirm the lower and higher Lewis’s acidity of coordinatively unsaturated Zr sites on linker defects in the UiO-66 structure when electron-withdrawing and electron-donating groups are, respectively, included in a terephthalate moiety, whilst the Brønsted acidity of zirconium oxo-cluster remains almost unchanged.